Health and Wellness–Related Travel: A Scoping Study of the Literature in 2010-2018. (May 2021) - Kemppainen, Laura; Koskinen, Veera; Bergroth, Harley; Marttila, Eetu; Kemppainen, Teemu
Health and wellness–related travel, also known as medical tourism, is a topical phenomenon with a wide range of effects in both local and transnational contexts. This scoping study examines the literature on this phenomenon from the perspective of travelers. The literature search was conducted using three databases (EBSCOhost, Web of Science, and SCOPUS) and covered the period from 2010 to 2018. The results show that the literature is divided into two academic fields: social sciences and tourism. Travel from the Global North to the Global South still dominates the field of medical travel research, and studies on South-to-South or intra-regional travel are underrepresented. There is a need for a more in-depth qualitative understanding of travelers' lived experiences and for studies with more advanced quantitative methods and longitudinal research designs. We call for more interdisciplinary and theoretical approaches to health and wellness–related travel and propose a conceptual model that considers travelers' intent (medical/wellness) and status (patient/tourist).